Provision of cellular blood components to CMV‐seronegative patients undergoing allogeneic stem cell transplantation in the UK: survey of UK transplant centres. Issue 6 (15th September 2017) - Morton, S.; Peniket, A.; Malladi, R.; Murphy, M. F.
SUMMARY: Objectives: To identify current UK practice with regards to provision of blood components for cytomegalovirus (CMV)‐seronegative, potential, allogeneic stem cell recipients of seronegative grafts. Background: Infection with CMV remains a major cause of morbidity and mortality after allogeneic stem cell transplantation (aSCT). CMV transmission has been a risk associated with the transfusion of blood components from previously exposed donors, but leucocyte reduction has been demonstrated to minimise this risk. In 2012, the UK Advisory Committee for the Safety of Tissues and Organs (SaBTO) recommended that CMV‐unselected components could be safely transfused without increased risk of CMV transmission. Methods: We surveyed UK aSCT centres to establish current practice. Results: Fifteen adult and seven paediatric centres (75%) responded; 22·7% continue to provide components from CMV‐seronegative donors. Reasons cited include the continued perceived risk of CMV transmission by blood transfusion, its associated morbidity and concerns regarding potential for ambiguous CMV serostatus in seronegative potential transplant recipients due to passive antibody transfer from CMV‐seropositive blood donors, leading to erroneous donor/recipient CMV matching at transplant. Conclusions: The survey demonstrated a surprisingly high rate (22.7%) of centres continuing to provide blood components from CMV‐seronegative donors despite SaBTO guidance.